REMOTE SENSING AND GIS APPLICATION ON FOREST COVER CHANGE DETECTION IN KIM TIEN COMMUNE, KIM BOI DISTRICT, HOA BINH PROVINCE FROM 1995 TO 2018 - Quang Bao, Tran; Thi Hue, Nguyen; Sy Hoa, Le (Journal of Forestry Science and Technology, 2019)
Remote sensing technology and GIS are considered as an effective and objective tool in monitoring and evaluating natural resources, especially in the detection of forest cover change. In this study, Landsat 5 TM satellite images in 1995, 2002, 2011 and Landsat 8 OLI/TIRS in 2018 were used to classify and detect the areas of forest change in Kim Tien commune, Kim Boi district, Hoa Binh province. NDVI (Normalized difference vegetation index) was employed to classify the forest cover from downloaded satellite imagery after pre-processing. The study has constructed a database and maps about forest cover for 4 different years 1995, 2002, 2011, 2018 with the accuracy greater than 75%, maps of forest cover change during 4 periods 1995 – 2002, 2002 – 2011, 2011 – 2018 and 1995 – 2018. The results showed that the total area of forest cover increased slightly, strongly fluctuated in the first period of 1995 – 2011, unevenly distributed and scattered throughout the entire commune. The forest cover decrease was concentrated mainly near residential areas, tended to expand gradually along the margin, especially according to the development of roads in the Southwest. Drivers of forest cover increased during the period 1995 – 2018 were the effective applications of forest plantation project, management, and protection.